Implementation of land acquisition for development of public interest: Analytical study on the construction of bypass road facilities to the Mandalika special economic zone - Sumiati, Lilik (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This study aims to determine the procedures for implementing land acquisition for constructing the Lombok International Airport ByPass road to the Land Acquisition Area for constructing the Lombok International Airport ByPass road to the Mandalika Special Economic Zone. Methods: This study uses empirical legal research with the statutory, conceptual, and sociological approaches. The data types in this study are primary and secondary, while the data sources use library research and field research. Techniques and ways of obtaining data are by conducting interviews and observations. The purpose of this study is to find out the procedures for implementing land acquisition for the construction of the Lombok International Airport ByPass road to the Mandalika Special Economic Zone, and to find out the inhibiting factors in this activity. Findings: The procedure for implementing land acquisition for the construction of the Lombok International Airport By Pass to the Mandalika Special Economic Zone as stipulated in Law Number 11 of 2020 Ciptaker regulates 4 (four) stages of acquisition starting from planning, preparation, implementation, and delivery of results. Conclusion: The land acquisition implementation committee has carried out land acquisition procedures following the provisions of the Laws and Regulations. The obstacles in constructing the Lombok International Airport By Pass road to the Mandalik Special Economic Zone include social, cultural, and economic factors. Novelty/Originality of this Study: An empirical examination of the land acquisition process for a major infrastructure project, specifically the Bypass Road from Lombok International Airport to the Mandalika Resort Special Economic Zone, employs a multifaceted approach encompassing legislative, conceptual, and sociological perspectives. This study uniquely identifies and analyzes the social, cultural, and economic barriers affecting the land acquisition process, providing insights into community dynamics and compensation issues within the context of Indonesian agrarian law and development.